Wheat Grain Yield Response to Seeding Rate in 2023-2024 - Romulo P. Lollato; Nicolas Giordano; Jazmin Gastaldi; Jorge Romero Soler; Luiz Otavio Pradella (Kansas Agricultural Experiment Station Research Reports, 2025)
Wheat response to seeding rate varies and depends on resource availability during the growing season (e.g., fertility, moisture, and temperature). Our objective was to evaluate winter wheat population and grain yield responses to seeding rate and its interaction with variety. The wheat varieties tested were WB4792, Langin, WB4422, and KS Big Bow in the trial conducted in Leoti (western KS), and all but Langin in the trial conducted in Belleville (north central KS). The trial included five seeding rates increasing exponentially from 100,000 to 1,600,000 seeds per acre. The trials were established after a long summer fallow in sorghum residue during late September 2023. Growing season total precipitation ranged from 11.1 to 15.4 inches. There were significant effects of seeding rate on final stand count, with greater rates resulting in greater stand counts; however, final stand count was closer to the target in lower seeding rates. At both locations, grain yield was affected independently by seeding rate and by variety, but not by their interaction, suggesting that varieties performed similarly as a function of seeding rate. In Belleville, yields ranged from 53.4 to 85.6 bushels per acre as a function of seeding rate, whereas in Leoti the range was 66.7 to 92.7 bushels per acre. At both sites, grain yield increased from the lowest seeding rate to 800,000 seeds per acre, plateauing thereafter. The variety KS Big Bow was the highest-yielding variety across sites. In Belleville, the highest yield of KS Big Bow could be attributed to the presence of wheat streak mosaic virus in the study site. Results here suggest that wheat yield varied as a function of variety and seed rate separately, highlighting opportunities to manage both variables independently.
Keywords: wheat; seeding rate; intensive management; crop density; yield contest